From traditional to digital: empowering sun mixture through University-community development participatory action research - Lambert, A.D.A.; Uthayakumar, A.D.A.; Bandara, A.M.S.L.; Bamunusinghe, B.A.I.K.; Geerththana, B.; Wijerathna, C.N.; Wickramasinghe, D.P.A.M.; Dissanayake, D.O.; Kodithuwakku, H.K.W.T.; Dilogini, S. (Rajarata University of Sri Lanka, 2024)
Sun Mixture, a Micro Small and Medium Enterprise (MSME), faces significant challenges due to its limited digital presence and reliance on traditional sales methods. This has resulted in a restricted market reach, diminished brand visibility, and missed growth opportunities. The lack of technology integration further hinders competitiveness in the modem marketplace. To address these challenges, marketing specialization students from the University of Jaffna conducted participatory action research with the objective of improving sales through online channels, enhancing customer engagement both locally and internationally, and increasing brand awareness. This research employed narrative inquiry to gather personal stories and insights that highlight the transformation of traditional marketing-based MSMEs towards a digital ecosystem. Photovoice allowed participants to visually document community strengths and challenges through photography, fostering in-depth discussions. Additionally, focus group discussions facilitated collective insights among stakeholders, whereas participatory mapping created visual representations of the spatial and social aspects of the environment. Researchers have identified critical issues, such as the lack of accessible online product details (ingredients and pricing), which are essential for customer decision-making, as well as the absence of customer reviews and online payment options, limiting transaction flexibility. The findings underscore the need for enhanced staff awareness of digital marketing techniques, overcoming resistance to digital business practices, and developing infrastructure to support online sales and engagement. The research also identified the importance of active social media engagement, effective content strategies to improve customer interaction, and the necessity of a fully optimized website for facilitating transactions. Practical implications include ongoing improvements to websites and social media content to maintain relevance, leveraging interactive features for customer feedback and loyalty-building, and forging partnerships with local delivery services to streamline online orders. In conclusion, researchers have established social media platforms for Sun Mixture, including Facebook, Instagram, TikTok, and WhatsApp. These initiatives significantly improved sales and enhanced brand awareness, demonstrating the effectiveness of digital solutions in fostering the growth of sun mixtures in the digital era.
Keywords: Digital transformation; Micro small and medium enterprises; Narrative inquiry; Participatory action research; Photo voice